Classroom Discourse, Smart Power Strategies, and Learner Engagement in Nepalese EFL Classrooms (Siddhajyoti Interdisciplinary Journal, 2026)
This paper analyzes how the classroom discourse and smart power strategies can contribute to enhancing learner engagement in EFL classrooms. The use of smart power is relevant not only in politics and governance but also in educational settings to create a better environment for the active participation of English language learners. Therefore, employing the qualitative content analysis method, I reviewed books and articles about smart power, classroom discourse, and learner engagement available in Google Scholar, ProQuest, and open sources and then analyzed the contents in relation to English language teaching and learning in the context of secondary schools of Nepal. As the theoretical foundation, Foucault’s archeology of knowledge and Bourdieu’s cultural capital theory helped me to contextualize and clarify the concept of smart power in ELT. The findings indicate that inclusive discourse and smart power strategies can motivate learners to be engaged in language learning with appropriate levels of support and challenge. Thus, this study will be supportive for English language teachers to engage all types of learners in language learning activities.